Confirmation on Status of Chaetocnema basalis (Coleoptera: Chrysomellidae) as A Vector of Stewart Wilt Disease - Heri Widodo; Arman Wijonarko; Witjaksono Witjaksono; Suputa Suputa (Universitas Gadjah Mada, 2017)
Chaetocnema pulicaria and C. denticulata are recognized as vectors of Stewart wilt disease caused by Pantoea stewartii on maize. These insects have not been reported yet in Indonesia, but Stewart wilt disease has been reported in Java and Sumatera Islands. Genus Chaetocnema which presented in Indonesia is C.basalis. It is not cleared whether C. basalis is a vector for Stewart wilt disease like C. pulicaria and C. denticulata. This reseach was aimed to conduct the confirmation on status whether C. basalis have a role as vector of Stewart wilt disease on maize or not. C. basalis imago were collected from maize growing areas in Yogyakarta, and then starved for 24 h. Treatments were applied by placing imago of C. basalis on infected-P. stewartii plants for 72 h. Five insects were then transferred to each plot of healthy plant (1 plot consisted of 5 plants) for 72 h. For control, imago of C. basalis were put on healthy plants for 72 h and five insects were then transferred to other healthy plant (1 plot consisted of 5 plants) for 72 h. Each treatment was repeated three times. On the fifteenth days after transmission, PCR assays were carried out on leaf samples and isolates of bacteria. All sampled leaves analysis showed that there were no Stewart wilt diseases transmission based on PCR assay and bacterial isolates. This concluded that C. basalis is not a vector for Stewart wilt disease on maize. IntisariChaetocnema pulicaria dan C. denticulata merupakan serangga vektor penyakit layu stewart yang disebabkan oleh bakteri Pantoea stewartii pada tanaman jagung. Kedua serangga ini belum pernah dilaporkan keberadaannya di Indonesia tetapi penyakit layu stewart telah ditemukan di pulau Jawa dan pulau Sumatera. Serangga Genus Chaetocnema yang ada di Indonesia adalah Chaetocnema basalis. C. basalis belum diketahui secara pasti sebagai vektor penyakit layu stewart seperti halnya C. pulicaria dan C. denticulata. Penelitian ini bertujuan untuk melakukan konfirmasi status apakah C. basalis berperan sebagai vektor penyakit layu stewart pada tanaman jagung atau tidak. Serangga uji berupa imago C. basalis yang dikoleksi dari pertanaman jagung di Yogyakarta, lalu dilaparkan selama 24 jam. Pengujian perlakuan dilakukan dengan menempatkan imago C. basalis pada tanaman terserang P. stewartii selama 72 jam. Kemudian dipindahkan pada tanaman sehat sejumlah 5 ekor per plot tanaman bersungkup (1 plot terdiri dari 5 tanaman) selama 72 jam. Perlakuan kontrol dilakukan dengan menempatkan imago C. basalis pada tanaman sehat selama 72 jam, kemudian dipindahkan pada tanaman sehat yang lain sejumlah 5 ekor per plot tanaman bersungkup (1 plot terdiri dari 5 tanaman) selama 72 jam. Masing-masing perlakuan diulang sebanyak tiga kali. Pada hari ke-15 setelah penularan, dilakukan uji PCR daun tanaman sampel dan isolat bakteri. Hasil pengujian semua sample daun menunjukkan negatif sehingga dipastikan bahwa C. basalis bukan merupakan vektor penyakit layu stewart pada tanaman jagung.